Definitory characteristics validation of the caregiver role fatigue diagnosis in Primary Care - Beatriz Álvarez Embarba; Alicia Quintano Pintado; Pilar Rabadán Carrasco (Fundación para el Desarrollo de la Enfermería, 2012)
Introduction: The nursing diagnostic "Fatigue in the performance of the roll of caregiver "have thirty and three definitories characteristics. The test of Zarit is not including between these definitories characteristics but an indicating faithful of the fatigue of the caretaker has demonstrate To analyze as they are the characteristics definitorias, including the Zarit, that better they predict the diagnostic "Fatigue in the performance roll del caregiver" in primary attention. Material and methods: Cross-sectional descriptive study Population: the total of the 57 caregivers of the immobilized patients. The collection of data was made by means of interview structured to the caretakers with the Zarit and the definitories characteristics of I diagnose fatigue roll of the caregiver. Descriptive, unvaried and multivariate statistical analysis was made with the statistical package Spss.10.0. Results: The final model of the logistic regression to value the variable predictors of the fatigue caregiver roll was the made up of positive the Zarit variables and the distintive characteristic preocupation by the cares with exactitude of 95.6% with one p> =0,001. Conclusions: These results could suggest the implantation of the Zarit like distintive characteristic as well as reduce to the number of characteristics definitorias.